Resolving Conflicts, Building Peace: Narratives of Mediators at the Grassroots - Melencion Jr., Eleuterio; Sabijon, Dodelon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the lived experiences of Lupon Tagapamayapa chairpersons in mediating community disputes in selected barangays of Buenavista, Bohol. It was anchored on the Theory of Conflict and Resolution, Decision Theory, and Self-Efficacy Theory to explain the dynamics of grassroots conflict resolution, decision-making, and mediator resilience. Using a qualitative phenomenological design, the study gathered data through a validated researcher-made interview guide administered through individual interviews and a focused group discussion. The respondents were ten Lupon Tagapamayapa chairpersons selected through purposive sampling based on their years of service, current residence and work in their barangays, and voluntary participation. Data were analyzed using transcendental phenomenological analysis. The findings revealed that mediation at the barangay level was both meaningful and challenging. Positive experiences were reflected in the themes Healing Justice: Where Compassion Meets Resolution and Silent Architects of Daily Harmony, showing that mediators valued reconciliation, restored relationships, and the preservation of community peace. Negative experiences emerged in When Land Becomes Legacy and Liability and Bloodlines and Battle Lines: A Kinship Divided, indicating that land and family disputes were among the most difficult cases to mediate because of their emotional, relational, and social complexities. The challenges encountered were expressed through Wisdom in Stillness: The Quiet Power of Calm and Clarity and Grace in Mediation: Faith, Fellowship, and the Soul of Resolution, highlighting the importance of calmness, fairness, emotional control, empathy, faith, and peer support. The study concluded that barangay mediation is not merely a procedural duty but a deeply human peacebuilding practice grounded in compassion, fairness, and trust. It recommends continuous training in mediation, emotional intelligence, and conflict transformation, along with stronger institutional support and values-based approaches to strengthen grassroots dispute resolution. The study is closely aligned with SDG 16 on Peace, Justice, and Strong Institutions and SDG 11 on Sustainable Cities and Communities. Its sustainability impact lies in strengthening community harmony, local governance, and institutional capacity for peaceful and accessible justice at the grassroots level.
Keywords: Barangay Justice, Community Disputes, Conflict Resolution, Grassroots Mediation, Lived Experiences, Lupon Tagapamayapa, Peacebuilding, Self-Efficacy